Lustmord : sexual murder in Weimar Germany - Tatar, Maria, 1945- 1945- (Princeton Univ. Press, 1995)
In a book that confronts our society's obsession with violence, Maria Tatar seeks the meaning behind one of the most disturbing images of twentieth-century Western culture: the violated female corpse. This image is so prevalent in painting, literature, film, and, most recently, in mass media, that we rarely question what is at stake in its representation. Tatar, however, challenges us to consider what is taking place - both artistically and socially - in the construction and circulation of scenes depicting sexual murder. In examining images of sexual murder (Lustmord), she produces a riveting study of how art and murder have intersected in the sexual politics of culture from Weimar Germany to the present.